Grouting material based on covalent organic framework energy absorption and preparation method and application thereof

By using covalent organic frame single crystals in the grouting material and other additives, the problem of insufficient impact resistance in the impact pressure tunnel is solved, and the efficient impact resistance and mechanical properties of the grouting material are improved, which is suitable for surrounding rock control of coal mine tunnels.

CN118894699BActive Publication Date: 2025-03-14CCTEG COAL MINING RES INST +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410939543.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-12
Publication Date
2025-03-14
Estimated Expiration
2044-07-12

AI Technical Summary

Technical Problem

The existing grouting and reinforcement technology has insufficient impact resistance in impact ground pressing tunnels, making it difficult to effectively control surrounding rocks, resulting in a major threat to the safety production of coal mines.

Method used

The grouting material based on the energy absorption of covalent organic frame is used, and the impact resistance, mechanical properties, bond strength and fluidity of the grouting material are improved by combining the covalent organic frame single crystal with premature strength agents, coagulant agents, toughening agents, water retention agents, reinforcement agents and iron aluminate clinker gelling materials.

Benefits of technology

While reducing production costs, it significantly improves the impact resistance and mechanical properties of grouting materials, enhances its bond strength with coal rock mass, improves fluidity, and is suitable for surrounding rock control in impact ground-pressed coal mine tunnels.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118894699B_ABST
    Figure CN118894699B_ABST
Patent Text Reader

Abstract

The present application proposes a grouting material based on covalent organic framework energy absorption, and its preparation method and application, wherein the grouting material based on covalent organic framework energy absorption includes the following components in parts by weight: 4-6 parts of covalent organic framework single crystals, 0.8-1.2 parts of early strength agent, 0.4-0.6 parts of coagulant, 0.4-0.6 parts of toughening agent, 0.24-0.36 parts of water retention agent, 0.8-1.2 parts of reinforcing agent, and 80-120 parts of ferroaluminate clinker gelling material. The grouting material based on covalent organic framework energy absorption of the present application uses covalent organic framework single crystals in combination with early strength agent, coagulant, toughening agent, water retention agent, reinforcing agent and ferroaluminate clinker gelling material, which can reduce the production cost of the grouting material while improving the impact resistance, mechanical properties, bonding strength and fluidity of the grouting material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of grouting reinforcement, and in particular to a grouting material based on covalent organic framework energy absorption, and a preparation method and application thereof. Background Art

[0002] Rock burst seriously threatens the safe and efficient production of coal mines in my country, causing sudden and severe destruction of the rock mass around the tunnel or working face due to the instantaneous release of elastic deformation energy, often accompanied by coal and rock mass ejection, loud noises and air waves. It is very destructive and is one of the major disasters in coal mines. It is generally believed that rock burst will occur when the stiffness of the mine structure is greater than the stiffness of the surrounding rock, that is, when the energy stored in the system is greater than the energy consumed in destruction and movement. The grouting reinforcement method has achieved good control effects in the application of non-rock burst tunnels, but in rock burst tunnels, its insufficient impact resistance has become a "bottleneck" problem that restricts the control of surrounding rock in rock burst coal mine tunnels.

[0003] Therefore, it is urgent to develop a new type of impact-resistant high-performance grouting material suitable for surrounding rock control in coal mine tunnels with rock burst, so that it has at least good impact resistance. Summary of the invention

[0004] In view of this, one purpose of the present application is to provide a grouting material based on covalent organic framework energy absorption, by using covalent organic framework single crystals in combination with early strength agents, accelerators, toughening agents, water retention agents, reinforcing agents and ferroaluminate clinker cementitious materials, which can reduce the production cost of the grouting material while improving the impact resistance, mechanical properties, bonding strength and fluidity of the grouting material.

[0005] Another object of the present application is to provide a method for preparing a grouting material based on covalent organic framework energy absorption.

[0006] Another object of the present application is to provide an application of a grouting material based on covalent organic framework energy absorption.

[0007] To achieve the above-mentioned objectives, the first aspect of the present application proposes a grouting material based on covalent organic framework energy absorption, comprising the following components in parts by weight: 4-6 parts of covalent organic framework single crystals, 0.8-1.2 parts of early strength agent, 0.4-0.6 parts of accelerator, 0.4-0.6 parts of toughening agent, 0.24-0.36 parts of water retaining agent, 0.8-1.2 parts of reinforcing agent, and 80-120 parts of ferroaluminate clinker cementitious material.

[0008] Preferably, the grouting material based on covalent organic framework energy absorption includes the following components in parts by weight: 4.5-5.5 parts of covalent organic framework single crystals, 0.9-1.1 parts of early strength agent, 0.45-0.55 parts of accelerator, 0.45-0.55 parts of toughening agent, 0.27-0.33 parts of water retaining agent, 0.9-1.1 parts of reinforcing agent, and 90-110 parts of ferroaluminate clinker cementitious material.

[0009] Further preferably, the grouting material based on covalent organic framework energy absorption comprises the following components in parts by weight: 5 parts of covalent organic framework single crystals, 1 part of early strength agent, 0.5 parts of accelerator, 0.5 parts of toughening agent, 0.3 parts of water retaining agent, 1 part of reinforcing agent, and 100 parts of ferroaluminate clinker cementitious material.

[0010] In some embodiments, the covalent organic framework single crystal has micropores and / or mesopores, and the covalent organic framework single crystal has at least one of the following characteristics:

[0011] (1) Specific surface area is 100-1500m 2 / g;

[0012] (2) The average pore size of the micropores is 1-2 nm;

[0013] (3) The average pore size of the mesopores is 2-50 nm;

[0014] (4) The porosity is 70-90%.

[0015] In some embodiments, the early strength agent includes at least one of cesium chloride, cesium sulfide, and cesium nitrate.

[0016] Preferably, the early strength agent consists of cesium chloride, cesium sulfide and cesium nitrate, and the mass ratio of cesium chloride, cesium sulfide and cesium nitrate is 1:(1.6-2.4):1.

[0017] In some embodiments, the coagulant includes at least one of sodium polyacrylate, polyethyleneimine, and sodium polyethylene sulfonate.

[0018] Preferably, the coagulant is composed of sodium polyacrylate, polyethyleneimine and sodium polyethylene sulfonate, and the mass ratio of sodium polyacrylate, polyethyleneimine and sodium polyethylene sulfonate is 1:(2.4-3.6):1.

[0019] In some embodiments, the toughening agent includes at least one of polyvinyl chloride-butadiene block copolymer nanoparticles and polyethylene-propylene-isoprene block copolymer nanoparticles.

[0020] Preferably, the toughening agent is composed of polyvinyl chloride-butadiene block copolymer nanoparticles and polyethylene-propylene-isoprene block copolymer nanoparticles, and the mass ratio of the polyvinyl chloride-butadiene block copolymer nanoparticles to the polyethylene-propylene-isoprene block copolymer nanoparticles is 1:(1.6-2.4).

[0021] In some embodiments, the water retaining agent includes at least one of sodium 3-chloro-2-hydroxypropane sulfonate and sodium carboxymethyl starch.

[0022] Preferably, the water retaining agent is composed of sodium 3-chloro-2-hydroxypropane sulfonate and sodium carboxymethyl starch, and the mass ratio of sodium 3-chloro-2-hydroxypropane sulfonate to sodium carboxymethyl starch is (2.4-3.6):1.

[0023] In some embodiments, the reinforcing agent includes at least one of nano-silicon carbide particles, polydopamine nano-particles, and nano-cobalt oxide particles.

[0024] Preferably, the reinforcing agent is composed of nano-silicon carbide particles, polydopamine nano-particles and nano-cobalt oxide particles, and the mass ratio of the nano-silicon carbide particles, the polydopamine nano-particles and the nano-cobalt oxide particles is 1:1:(4-6).

[0025] The second aspect of the present application proposes a method for preparing a grouting material based on covalent organic framework energy absorption, comprising:

[0026] The covalent organic framework single crystal, early strength agent, accelerator, toughening agent, water retaining agent, reinforcing agent and aluminoferrite clinker gelling material are mixed in a formula amount to obtain the grouting material based on covalent organic framework energy absorption.

[0027] In some embodiments, the method for preparing the grouting material based on the covalent organic framework energy absorption further comprises the step of preparing the covalent organic framework single crystal; the method for preparing the covalent organic framework single crystal comprises:

[0028] dissolving the carbon source in a solvent to obtain a uniform solution;

[0029] At least a portion of the uniform solution is subjected to an organic covalent reaction under the action of a catalyst, and then filtered and dried to obtain the covalent organic framework single crystal.

[0030] In some embodiments, the carbon source includes at least one of 4,4′-(1,10-phenanthroline-2,9-diyl)diphenylamine, tetrakis(4-formylphenyl)ethylene, and tetrakis(4-borylphenyl)ethylene.

[0031] In some embodiments, the solvent is a non-polar solvent.

[0032] In some embodiments, the method of dissolving the carbon source in the solvent includes at least one of heating, stirring, ultrasonic dispersion, and ball milling.

[0033] In some embodiments, the catalyst includes at least one of zinc chloride and stannous octoate.

[0034] In some embodiments, the amount of the catalyst used is 1-5 wt % of the amount of the carbon source used.

[0035] In some embodiments, the organic covalent reaction is performed in a microwave reaction tube.

[0036] In some embodiments, the temperature of the organic covalent reaction is 100-120° C., and the time of the organic covalent reaction is 1.5-3 h.

[0037] The third aspect of the present application relates to the application of the grouting material based on covalent organic framework energy absorption described in the present application or the grouting material based on covalent organic framework energy absorption prepared by the preparation method of the grouting material based on covalent organic framework energy absorption described in the present application in the field of surrounding rock control of coal mine tunnels with rock burst.

[0038] The grouting material based on covalent organic framework energy absorption described in this application can at least bring the following beneficial effects:

[0039] The use of covalent organic framework single crystals in combination with early strength agents, accelerators, toughening agents, water retaining agents, reinforcing agents and ferroaluminate clinker cementitious materials can reduce the production cost of grouting materials while improving the impact resistance, mechanical properties, bonding strength and fluidity of the grouting materials.

[0040] Specifically:

[0041] 1. The structure of the covalent organic framework single crystal creates a highly porous structure with a high specific surface area, which makes the interface area between the covalent organic framework single crystal and the ferroaluminate clinker cementitious material large and can absorb impact energy and impact work.

[0042] 2. Covalent organic framework single crystals are beneficial to improving the toughness and mechanical strength of grouting materials.

[0043] 3. The covalent organic framework single crystal presents a spherical shape, which can reduce the viscosity of the internal structure of the grouting material slurry and the friction between the particles, thereby significantly increasing the lubrication effect and improving the fluidity of the grouting material.

[0044] 4. Covalent organic framework single crystals have a large number of active sites, which can produce chemical bonding by coordinating with active groups such as hydroxyl and carboxyl groups on the surface of coal and rock masses, thereby improving the interfacial bonding strength between the grouting stone body and the coal and rock mass and improving the grouting reinforcement effect.

[0045] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0046] The above and / or additional aspects and advantages of the present application will become apparent and easily understood from the following description of the embodiments in conjunction with the accompanying drawings.

[0047] in:

[0048] Figure 1 This is a flow chart of a method for preparing a grouting material based on covalent organic framework energy absorption, showing an exemplary embodiment of the present application. DETAILED DESCRIPTION

[0049] The embodiments of the present application are described in detail below. The embodiments are exemplary and intended to be used to explain the present application, but should not be construed as limiting the present application.

[0050] In this application, the disclosure of numerical ranges includes all values ​​within the entire range and the disclosure of further subdivided ranges, including the endpoints and sub-ranges given in these ranges.

[0051] In this application, the raw materials, equipment, etc. involved, unless otherwise specified, are all raw materials and equipment that can be made through commercial channels or known methods; the methods involved, unless otherwise specified, are all conventional methods.

[0052] <Grouting materials based on covalent organic framework energy absorption>

[0053] The grouting material based on covalent organic framework energy absorption in the embodiment of the present application includes the following components in parts by weight: 4-6 parts of covalent organic framework single crystals, 0.8-1.2 parts of early strength agent, 0.4-0.6 parts of accelerator, 0.4-0.6 parts of toughening agent, 0.24-0.36 parts of water retaining agent, 0.8-1.2 parts of reinforcing agent, and 80-120 parts of ferroaluminate clinker cementitious material.

[0054] In the embodiments of the present application, the role of the covalent organic framework single crystal is to serve as the structural cross-linking point and stress concentration point of the grouting material, and the high specific surface area property makes it serve as the heterogeneous nucleation site for the hydration crystallization of the cementitious material; the role of the early strength agent is to promote the rapid increase of the early strength of the grouting material; the role of the accelerator is to promote the solidification and hydration hardening of the grouting material; the role of the toughening agent is to improve the toughness of the grouting material; the role of the water-retaining agent is to avoid the loss of water during the flow and penetration of the grouting slurry in the coal rock cracks, and reduce its fluidity loss; the role of the reinforcing agent is to increase the bonding effect between the grouting slurry and the coal body; the role of the ferroaluminate clinker cementitious material is to serve as the matrix of the grouting material, providing a stone body matrix for the hydration crystallization of the grouting material.

[0055] In the grouting material based on covalent organic framework energy absorption in the embodiments of the present application, the ratio of the components such as covalent organic framework single crystals, early strength agent, accelerator, toughening agent, water retention agent, reinforcing agent, ferroaluminate clinker cementitious material is within the above-mentioned range, which can reduce the production cost of the grouting material while improving the impact resistance, mechanical properties, bonding strength and fluidity of the grouting material, making it suitable for surrounding rock control of coal mine tunnels with rock burst. At the same time, within the above range defined in the present application, the more the amount of aluminoferrite clinker cementitious material is used, the faster the hydration rate of the cementitious material is, and the shorter the setting and curing time is; the less the amount of aluminoferrite clinker cementitious material is used, the slower the hydration rate of the cementitious material is, and the longer the setting and curing time is; the more the amount of covalent organic framework single crystals is used, the more physical crosslinking points and stress concentration points of the internal structure of the grouting material are, the higher the degree of hydration crystallization is, and the higher the compressive strength of the grouting material is; the less the amount of covalent organic framework single crystals is used, the fewer physical crosslinking points and stress concentration points of the internal structure of the grouting material are, the lower the degree of hydration crystallization is, and the lower the compressive strength of the grouting material is; the amount of early strength agent is The more the amount of early strength agent is used, the higher the early strength of the grouting material; the less the amount of early strength agent is used, the lower the early strength of the grouting material; the more the amount of accelerator is used, the faster the setting time of the grouting material; the less the amount of accelerator is used, the slower the setting time of the grouting material; the more the amount of toughening agent is used, the higher the flexural strength of the grouting material; the less the amount of toughening agent is used, the lower the flexural strength of the grouting material; the more the amount of water-retaining agent is used, the higher the fluidity of the grouting material; the less the amount of water-retaining agent is used, the lower the flexural strength of the grouting material; the more the amount of reinforcing agent is used, the higher the bonding strength of the grouting material; the less the amount of reinforcing agent is used, the lower the bonding strength of the grouting material.

[0056] In the embodiments of the present application, in the grouting material based on the covalent organic framework energy absorption, if the ratio of each component exceeds the above range, it will have a negative impact on the improvement of the impact resistance, mechanical properties, bonding strength and fluidity of the grouting material. For example, if the content of ferroaluminate clinker cementitious material is too high, the setting time of the grouting material is too short, and it is easy to produce instant setting phenomenon when it is used on site, and it is too late to be injected into the cracks of the coal mine tunnel; if the content of ferroaluminate clinker cementitious material is too low, the setting time of the grouting material is too long, and it will not solidify for a long time after being injected into the cracks of the coal mine tunnel, and it cannot play the role of grouting reinforcement; if the content of covalent organic framework single crystal is too high, it will lead to a large amount of enrichment and agglomeration in the matrix, poor dispersibility, and the compressive strength of the grouting material will decrease; if the content of covalent organic framework single crystal is too low, the density of physical crosslinking points and stress concentration points is too low, and the strength effect of the grouting material cannot be improved.

[0057] As a preferred example, the above-mentioned grouting material based on covalent organic framework energy absorption includes the following components in proportions by weight: 4.5-5.5 parts of covalent organic framework single crystals, 0.9-1.1 parts of early strength agent, 0.45-0.55 parts of accelerator, 0.45-0.55 parts of toughening agent, 0.27-0.33 parts of water retaining agent, 0.9-1.1 parts of reinforcing agent, and 90-110 parts of ferroaluminate clinker cementitious material.

[0058] As a more preferred example, the above-mentioned grouting material based on covalent organic framework energy absorption includes the following components in parts by mass: 5 parts of covalent organic framework single crystals, 1 part of early strength agent, 0.5 parts of accelerator, 0.5 parts of toughening agent, 0.3 parts of water retaining agent, 1 part of reinforcing agent, and 100 parts of ferroaluminate clinker cementitious material.

[0059] In the embodiments of the present application, the ferroaluminate clinker cementitious material is also called "ferroaluminate cement" or "rapid hardening ferroaluminate cement", which is a hydraulic gel material with high early strength, code-named R·FAC, which is made by grinding raw materials of appropriate composition, the cement clinker with anhydrous calcium sulphoaluminate, iron phase and dicalcium silicate as the main mineral components, limestone, and an appropriate amount of gypsum together.

[0060] As an optional example, the ferroaluminate clinker cementitious material of the embodiment of the present application complies with the provisions on fast-hardening ferroaluminate cement in "JC 933-2003 Fast-hardening sulphoaluminate cement Fast-hardening ferroaluminate cement".

[0061] Illustratively, the composition of the ferroaluminate clinker cementitious material of the embodiment of the present application meets the requirements of Table 1.

[0062] Table 1

[0063] Cement Type Clinker + gypsum, wt% Limestone, wt% Rapid hardening ferroaluminate cement ≧85 ≦15

[0064] It should be noted that the above alumina-ferrocement clinker cementitious materials that comply with the provisions of "JC 933-2003 Rapid Hardening Sulphoaluminate Cement Rapid Hardening Alumina-ferrocement" are only exemplary and cannot be used as the sole limitation for the embodiments of the present application. In the art, any alumina-ferrocement clinker cementitious materials that can be used to achieve the technical effects of the present application can be used in the present application.

[0065] In some embodiments, the covalent organic framework single crystal has micropores and / or mesopores.

[0066] In some embodiments, the covalent organic framework single crystal has at least one of the following characteristics:

[0067] (1) Specific surface area is 100-1500m 2 / g;

[0068] (2) The average pore size of the micropores is 1-2 nm;

[0069] (3) The average pore size of the mesopores is 2-50 nm;

[0070] (4) The porosity is 70%-90%.

[0071] Exemplarily, the specific surface area of ​​the covalent organic framework single crystal includes but is not limited to 100 m 2 / g, 200m 2 / g、300m 2 / g, 400m 2 / g、500m 2 / g、600m 2 / g、700m 2 / g、800m 2 / g、900m 2 / g、1000m 2 / g、1100m 2 / g、1200m 2 / g、1300m 2 / g、1400m 2 / g or 1500m 2 / g, etc.

[0072] For example, the average pore diameter of the micropores of the covalent organic framework single crystal includes, but is not limited to, 1 nm, 1.25 nm, 1.5 nm, 1.75 nm, or 2 nm.

[0073] Exemplarily, the average pore diameter of the mesopores of the covalent organic framework single crystal includes, but is not limited to, 2 nm, 10 nm, 20 nm, 30 nm, 40 nm or 50 nm, etc.

[0074] For example, the porosity of the covalent organic framework single crystal includes, but is not limited to, 70%, 75%, 80%, 85% or 90%.

[0075] In the embodiments of the present application, the covalent organic framework single crystal is also referred to as a covalent organic framework (COF).

[0076] In the embodiments of the present application, the covalent organic framework (COF) is connected by covalent bonds, so that its structure is more stable, not susceptible to external impact and damage, forming the effect of cross-linking points, and improving the stability of the material. At the same time, the structure of the covalent organic framework (COF) creates a highly porous structure, so that it has an ultra-large specific surface area (the specific surface area can reach 1500 square meters / gram), and the high specific surface area increases the interface area, increases the interface energy, and increases the impact resistance of the grouting material.

[0077] In some embodiments, the early strength agent includes but is not limited to at least one of cesium chloride, cesium sulfide, cesium nitrate, and the like.

[0078] As a preferred example, the early strength agent consists of cesium chloride, cesium sulfide and cesium nitrate.

[0079] Exemplarily, when the early strength agent consists of cesium chloride, cesium sulfide and cesium nitrate, the mass ratio of cesium chloride, cesium sulfide and cesium nitrate is 1:(1.6-2.4):1, including but not limited to 1:1.6:1, 1:1.8:1, 1:2:1 or 1:2.2:1, etc., preferably 1:2:1.

[0080] In some embodiments, the coagulant includes but is not limited to at least one of sodium polyacrylate, polyethyleneimine, sodium polyethylene sulfonate, and the like.

[0081] As a preferred example, the coagulant is composed of sodium polyacrylate, polyethyleneimine and sodium polyethylene sulfonate.

[0082] Exemplarily, when the coagulant consists of sodium polyacrylate, polyethyleneimine and sodium polyethylene sulfonate, the mass ratio of sodium polyacrylate, polyethyleneimine and sodium polyethylene sulfonate is 1:(2.4-3.6):1, including but not limited to 1:2.7:1, 1:3:1 or 1:3.3:1, etc., preferably 1:3:1.

[0083] In some embodiments, the toughening agent includes, but is not limited to, at least one of polyvinyl chloride-butadiene block copolymer nanoparticles, polyethylene-propylene-isoprene block copolymer nanoparticles, and the like.

[0084] As a preferred example, the toughening agent is composed of polyvinyl chloride-butadiene block copolymer nanoparticles and polyethylene-propylene-isoprene block copolymer nanoparticles.

[0085] Exemplarily, when the toughening agent is composed of polyvinyl chloride-butadiene block copolymer nanoparticles and polyethylene-propylene-isoprene block copolymer nanoparticles, the mass ratio of the vinyl chloride-butadiene block copolymer nanoparticles and the polyethylene-propylene-isoprene block copolymer nanoparticles is 1:(1.6-2.4), including but not limited to 1:1.8, 1:2 or 1:2.2, etc., preferably 1:2.

[0086] In some embodiments, the water retaining agent includes but is not limited to at least one of sodium 3-chloro-2-hydroxypropane sulfonate, sodium carboxymethyl starch, and the like.

[0087] As a preferred example, the water retaining agent is composed of sodium 3-chloro-2-hydroxypropane sulfonate and sodium carboxymethyl starch.

[0088] Exemplarily, when the water retaining agent is composed of sodium 3-chloro-2-hydroxypropane sulfonate and sodium carboxymethyl starch, the mass ratio of sodium 3-chloro-2-hydroxypropane sulfonate and sodium carboxymethyl starch is (2.4-3.6):1, including but not limited to 2.7:1, 3:1 or 3.3:1, etc., preferably 3:1.

[0089] In some embodiments, the reinforcing agent includes, but is not limited to, at least one of nano-silicon carbide particles, polydopamine nano-particles, nano-cobalt oxide particles, and the like.

[0090] As a preferred example, when the enhancer is composed of nano-silicon carbide particles, polydopamine nanoparticles and nano-cobalt oxide particles, the mass ratio of the nano-silicon carbide particles, the polydopamine nanoparticles and the nano-cobalt oxide particles is 1:1:(4-6), including but not limited to 1:1:4.5, 1:1:5 or 1:1:5.5, etc., preferably 1:1:5.

[0091] The grouting material based on covalent organic framework energy absorption in the embodiment of the present application can at least bring the following beneficial effects:

[0092] The use of covalent organic framework single crystals in combination with early strength agents, accelerators, toughening agents, water retaining agents, reinforcing agents and ferroaluminate clinker cementitious materials can reduce the production cost of grouting materials while improving the impact resistance, mechanical properties, bonding strength and fluidity of the grouting materials.

[0093] Specifically:

[0094] 1. The structure of the covalent organic framework single crystal creates a highly porous structure with a high specific surface area, which makes the interface area between the covalent organic framework single crystal and the ferroaluminate clinker cementitious material large and can absorb impact energy and impact work.

[0095] 2. Covalent organic framework single crystals are beneficial to improving the toughness and mechanical strength of grouting materials.

[0096] 3. The covalent organic framework single crystal presents a spherical shape, which can reduce the viscosity of the internal structure of the grouting material slurry and the friction between the particles, thereby significantly increasing the lubrication effect and improving the fluidity of the grouting material.

[0097] 4. There are a large number of unsaturated sites in the covalent organic framework single crystal, which can produce chemical bonding by coordinating with active groups such as hydroxyl and carboxyl groups on the surface of coal and rock, thereby improving the interfacial bonding strength between the grouting stone body and the coal and rock mass and improving the grouting reinforcement effect.

[0098] <Preparation method of grouting material based on covalent organic framework energy absorption>

[0099] The method for preparing the grouting material based on covalent organic framework energy absorption according to the embodiment of the present application can be used to prepare the grouting material based on covalent organic framework energy absorption according to the embodiment of the present application.

[0100] Figure 1 The following is a flow chart of a method for preparing a grouting material based on a covalent organic framework energy absorption according to an exemplary embodiment of the present application. Figure 1 Said preparation method comprises the following steps:

[0101] The covalent organic framework single crystal, early strength agent, accelerator, toughening agent, water retaining agent, reinforcing agent and ferroaluminate clinker cementitious material in a prescribed amount are mixed to obtain a grouting material based on covalent organic framework energy absorption.

[0102] It should be noted that in the embodiments of the present application, the covalent organic framework single crystal can be a commercially available product or homemade, as long as the technical effect of the present application can be achieved.

[0103] In some embodiments, in the method for preparing a grouting material based on covalent organic framework energy absorption in the embodiment of the present application, the covalent organic framework single crystal is obtained by a homemade method.

[0104] As an optional example, a method for preparing a covalent organic framework single crystal includes the following steps:

[0105] S101, dissolving a carbon source in a solvent to obtain a uniform solution.

[0106] In some embodiments, the carbon source includes but is not limited to at least one of 4,4′-(1,10-phenanthroline-2,9-diyl)diphenylamine, tetrakis(4-formylphenyl)ethylene, and tetrakis(4-boronic acid phenyl)ethylene.

[0107] As an optional example, the carbon source is composed of 4,4′-(1,10-phenanthroline-2,9-diyl)diphenylamine, tetrakis(4-formylphenyl)ethylene, and tetrakis(4-borylphenyl)ethylene.

[0108] Exemplarily, when the carbon source is composed of 4,4′-(1,10-phenanthroline-2,9-diyl)diphenylamine, tetrakis(4-formylphenyl)ethylene, and tetrakis(4-boronic acid phenyl)ethylene, the mass ratio of 4,4′-(1,10-phenanthroline-2,9-diyl)diphenylamine, tetrakis(4-formylphenyl)ethylene, and tetrakis(4-boronic acid phenyl)ethylene is (3.2-4.8):(1.6-2.4):(2.4-3.6), including but not limited to 3.2:2:3, 4.8:2:3, 3.6:2:3, 3.6:1.8:2.7, 4.4:2.1:3.2 or 4:2:3, etc., preferably 4:2:3.

[0109] In some embodiments, the solvent is a non-polar solvent.

[0110] Illustratively, the above-mentioned non-polar solvent includes but is not limited to at least one of carbon tetrachloride, hexafluoroisopropanol, dioxane, and the like.

[0111] As a preferred example, the non-polar solvent is a mixed solvent of carbon tetrachloride, hexafluoroisopropanol and dioxane.

[0112] Exemplarily, when the non-polar solvent is a mixed solvent of carbon tetrachloride, hexafluoroisopropanol and dioxane, the mass ratio of carbon tetrachloride, hexafluoroisopropanol and dioxane is 1:(2.4-3.6):(5.6-8.4), including but not limited to 1:2.7:7, 1:3.3:7, 1:3:6.3 or 1:3:7, etc., preferably 1:3:7.

[0113] In some embodiments, the mass ratio of the carbon source to the solvent is (16-24):(70-106), including but not limited to 16:88, 24:88, 20:90, 20:100 or 20:88, etc., preferably 20:88.

[0114] In some embodiments, the method of dissolving the carbon source in the solvent includes but is not limited to at least one of heating, stirring, ultrasonic dispersion, and ball milling.

[0115] As an optional example, the method of dissolving the carbon source in the solvent is heating.

[0116] Exemplarily, the heating temperature is 30-50°C, including but not limited to 30°C, 35°C, 40°C or 45°C, etc.

[0117] S102, subjecting at least part of the uniform solution obtained in step S101 to an organic covalent reaction under the action of a catalyst, followed by filtering and drying to obtain a covalent organic framework single crystal.

[0118] In some embodiments, the catalyst includes, but is not limited to, at least one of zinc chloride, stannous octoate, and the like.

[0119] As a preferred example, the catalyst is a composite catalyst composed of zinc chloride and stannous octoate.

[0120] Exemplarily, when the catalyst is a composite catalyst composed of zinc chloride and stannous octoate, the mass ratio of zinc chloride to stannous octoate is 1:(4.8-7.2), including but not limited to 1:5.4, 1:6.6 or 1:6, etc., preferably 1:6.

[0121] In some embodiments, the amount of the catalyst is 1-5wt% of the amount of the carbon source, including but not limited to 1wt%, 2wt%, 3wt%, 4wt% or 5wt%, etc. In the examples of the present application, the amount of the catalyst determines the specific surface area, micropores (<2nm) and mesopores (2-50nm), porosity, etc. of the covalent organic framework. Generally, the higher the amount of the catalyst, the larger the specific surface area and the higher the porosity.

[0122] In some embodiments, the organic covalent reaction is performed in a microwave reaction tube.

[0123] In some embodiments, the temperature of the organic covalent reaction is 100-120°C, including but not limited to 100°C, 105°C, 110°C, or 115°C.

[0124] In some embodiments, the time of the organic covalent reaction is 1.5-3 h, including but not limited to 1.8 h, 2.3 h, 2.5 h or 2.7 h, etc.

[0125] The preparation method of the grouting material based on covalent organic framework energy absorption in the embodiment of the present application is as follows: 4,4′-(1,10-phenanthroline-2,9-diyl)diphenylamine, tetra(4-formylphenyl)ethylene, tetra(4-boric acid phenyl)ethylene and other carbon sources are added to carbon tetrachloride, hexafluoroisopropanol, dioxane and other solvents, auxiliary heating is used to promote dissolution, and then zinc chloride, stannous octoate and other catalysts are added to carry out organic framework reaction in a microwave reaction tube to prepare a covalent organic framework single crystal with a high specific surface area. The prepared covalent organic framework single crystal, early strength agent, coagulant, toughening agent, water retention agent, reinforcing agent and the like are added to the ferroaluminate clinker gelling material to prepare a grouting material based on covalent organic framework energy absorption suitable for coal mine rock burst tunnels. In the composite grouting material, the prepared covalent organic framework single crystal has a highly porous structure and a high specific surface area. The interface area between the covalent organic framework single crystal and the ferroaluminate clinker is large, which can absorb impact energy and impact work. The prepared covalent organic framework single crystal has a fibrous structure, which is beneficial to improve the toughness and mechanical strength of the grouting material. At the same time, the prepared covalent organic framework single crystal presents a spherical shape, which reduces the viscosity of the internal structure of the grouting material slurry and the friction between the particles, thereby significantly increasing the lubrication effect and improving the fluidity of the grouting material. In addition, the prepared covalent organic framework single crystal has a large number of unsaturated sites, which can produce chemical bonding by coordinating with active groups such as hydroxyl and carboxyl groups on the surface of the coal rock mass, thereby improving the interface bonding strength between the grouting stone body and the coal rock mass and improving the grouting reinforcement effect. The preparation method is simple in process and low in cost. The prepared grouting material based on covalent organic framework energy absorption has outstanding impact resistance, excellent mechanical properties, high bonding strength and good fluidity, and is suitable for surrounding rock control of coal mine rock burst tunnels.

[0126] <Application of grouting materials based on covalent organic framework energy absorption>

[0127] The grouting material based on covalent organic framework energy absorption of the embodiment of the present application or the grouting material based on covalent organic framework energy absorption prepared by the preparation method of the grouting material based on covalent organic framework energy absorption of the embodiment of the present application can be widely used in the field of surrounding rock control of coal mine tunnels with rock burst.

[0128] Certain features of the present technology are further illustrated in the following non-limiting examples.

[0129] The aluminoferroic acid clinker cementitious materials involved in the following embodiments and comparative examples are all aluminoferroic acid clinker cementitious materials produced by Zibo Chuanfeng Building Energy-Saving Materials Factory.

[0130] Example 1 (the amount of catalyst used is the upper limit of the amount of carbon source used, 5 wt%)

[0131] (Grouting material based on covalent organic framework energy absorption)

[0132] The grouting material based on covalent organic framework energy absorption in this embodiment is composed of the following components by mass: 5 parts of covalent organic framework single crystal, 1 part of early strength agent, 0.5 parts of accelerator, 0.5 parts of toughening agent, 0.3 parts of water retaining agent, 1 part of reinforcing agent, and 100 parts of ferroaluminate clinker.

[0133] The specific surface area of ​​the covalent organic framework single crystal is 1440 m 2 / g; the covalent organic framework single crystal has micropores and mesopores, the average pore diameter of the micropores is 1.1nm, the average pore diameter of the mesopores is 5nm, and the porosity of the covalent organic framework is 89%.

[0134] The early strength agent is composed of cesium chloride, cesium sulfide and cesium nitrate, and the mass ratio of cesium chloride, cesium sulfide and cesium nitrate is 1:2:1.

[0135] The coagulant is composed of sodium polyacrylate, polyethyleneimine and sodium polyethylene sulfonate, and the mass ratio of sodium polyacrylate, polyethyleneimine and sodium polyethylene sulfonate is 1:3:1.

[0136] The toughening agent consists of polyvinyl chloride-butadiene block copolymer nanoparticles and polyethylene-propylene-isoprene block copolymer nanoparticles, and the mass ratio of the polyvinyl chloride-butadiene block copolymer nanoparticles to the polyethylene-propylene-isoprene block copolymer nanoparticles is 1:2.

[0137] The water retaining agent consists of sodium 3-chloro-2-hydroxypropane sulfonate and sodium carboxymethyl starch, and the mass ratio of sodium 3-chloro-2-hydroxypropane sulfonate to sodium carboxymethyl starch is 3:1.

[0138] The reinforcing agent consists of nano silicon carbide particles, polydopamine nano particles and nano cobalt oxide particles, and the mass ratio of the nano silicon carbide particles, the polydopamine nano particles and the nano cobalt oxide particles is 1:1:5.

[0139] (Preparation method of grouting material based on covalent organic framework energy absorption)

[0140] The preparation method of the grouting material based on the covalent organic framework energy absorption of this embodiment comprises the following steps:

[0141] Step S101, dissolving 20 parts by mass of a carbon source in 88 parts by mass of a solvent under heating at 50°C to obtain a uniform solution.

[0142] The carbon source is composed of 4,4′-(1,10-phenanthroline-2,9-diyl)diphenylamine, tetrakis(4-formylphenyl)ethylene, and tetrakis(4-boronic acid phenyl)ethylene, and the mass ratio of 4,4′-(1,10-phenanthroline-2,9-diyl)diphenylamine, tetrakis(4-formylphenyl)ethylene, and tetrakis(4-boronic acid phenyl)ethylene is 4:2:3.

[0143] The solvent is a mixed solvent of carbon tetrachloride, hexafluoroisopropanol and dioxane in a mass ratio of 1:3:7.

[0144] Step S102, adding 1 part by mass of a catalyst to 100 parts by mass of the uniform solution obtained in step S101, reacting at 110° C. for 2 hours in a microwave reaction tube, then filtering and drying to obtain a covalent organic framework single crystal.

[0145] The catalyst is a composite catalyst composed of zinc chloride and stannous octoate, and the mass ratio of zinc chloride to stannous octoate is 1:6.

[0146] Step S103, weigh 5 parts of the covalent organic framework single crystal obtained in step S102, 1 part of an early strength agent, 0.5 parts of a coagulant, 0.5 parts of a toughening agent, 0.3 parts of a water retaining agent, and 1 part of a reinforcing agent according to mass, add them to 100 parts of alumina-ferroferrate clinker cementitious material, mix in a dry powder mixer for 30 minutes, and obtain the present application.

[0147] Weigh 2 kg of the grouting material prepared in this embodiment, mix it evenly with deionized water in a mass ratio of 1:1, and test the bonding strength of the slurry with reference to the national standard GB / T29756-2013; prepare the slurry into a test block of 40 mm × 40 mm × 160 mm, and test the bonding strength of the slurry with reference to the national standard GB / T 17671-2021 to characterize the compressive strength of the material.

[0148] After testing, the impact resistance of the grouting material based on the covalent organic framework energy absorption in this embodiment is 7.8MJ / m 2The flexural strength is 14.3MPa, the compressive strength is 73MPa, the bonding strength is 2.5MPa, the fluidity is 37s, and the setting time is 21min.

[0149] Example 2 (the amount of catalyst used is the lower limit of the amount of carbon source used, 1 wt%)

[0150] This embodiment is basically the same as Embodiment 1, except that:

[0151] Grouting materials based on covalent organic framework energy absorption:

[0152] The specific surface area of ​​the covalent organic framework single crystal is 156m 2 / g; the covalent organic framework single crystal has micropores and mesopores, the average pore diameter of the micropores is 2.0nm, the average pore diameter of the mesopores is 47nm, and the porosity of the covalent organic framework is 71%.

[0153] In the preparation method of the grouting material based on the covalent organic framework energy absorption:

[0154] In step S102, the amount of catalyst used is 0.2 parts by mass.

[0155] Weigh 2 kg of the grouting material prepared in this embodiment, mix it evenly with deionized water in a mass ratio of 1:1, and test the bonding strength of the slurry with reference to the national standard GB / T29756-2013; prepare the slurry into a test block of 40 mm × 40 mm × 160 mm, and test the bonding strength of the slurry with reference to the national standard GB / T 17671-2021 to characterize the compressive strength of the material.

[0156] After testing, the impact resistance of the grouting material based on the covalent organic framework energy absorption in this embodiment is 4.6MJ / m 2 The flexural strength is 11.7MPa, the compressive strength is 49MPa, the bonding strength is 2.1MPa, the fluidity is 42s, and the setting time is 24min.

[0157] Example 3 (the amount of catalyst used is 3 wt% of the amount of carbon source used)

[0158] This embodiment is basically the same as Embodiment 1, except that:

[0159] Grouting materials based on covalent organic framework energy absorption:

[0160] The specific surface area of ​​the covalent organic framework single crystal is 1278m 2 / g; the covalent organic framework single crystal has micropores and mesopores, the average pore diameter of the micropores is 1.6nm, the average pore diameter of the mesopores is 35nm, and the porosity of the covalent organic framework is 81%.

[0161] In the preparation method of the grouting material based on the covalent organic framework energy absorption:

[0162] In step S102, the amount of catalyst used is 0.6 parts by mass.

[0163] Weigh 2 kg of the grouting material prepared in this embodiment, mix it evenly with deionized water in a mass ratio of 1:1, and test the bonding strength of the slurry with reference to the national standard GB / T29756-2013; prepare the slurry into a test block of 40 mm × 40 mm × 160 mm, and test the bonding strength of the slurry with reference to the national standard GB / T 17671-2021 to characterize the compressive strength of the material.

[0164] After testing, the impact resistance of the grouting material based on the covalent organic framework energy absorption in this embodiment is 6.9MJ / m 2 , flexural strength is 13.7MPa, compressive strength is 65MPa, bonding strength is 2.4MPa, fluidity is 40, and setting time is 22min.

[0165] Example 4 (the amount of catalyst used is 2 wt% of the amount of carbon source used)

[0166] This embodiment is basically the same as Embodiment 1, except that:

[0167] Grouting materials based on covalent organic framework energy absorption:

[0168] The specific surface area of ​​the covalent organic framework single crystal is 778m 2 / g; the covalent organic framework single crystal has micropores and mesopores, the average pore diameter of the micropores is 1.8nm, the average pore diameter of the mesopores is 42nm, and the porosity of the covalent organic framework is 75%.

[0169] In the preparation method of the grouting material based on the covalent organic framework energy absorption:

[0170] In step S102, the amount of catalyst used is 0.4 parts by mass.

[0171] Weigh 2 kg of the grouting material prepared in this embodiment, mix it evenly with deionized water in a mass ratio of 1:1, and test the bonding strength of the slurry with reference to the national standard GB / T29756-2013; prepare the slurry into a test block of 40 mm × 40 mm × 160 mm, and test the bonding strength of the slurry with reference to the national standard GB / T 17671-2021 to characterize the compressive strength of the material.

[0172] After testing, the impact resistance of the grouting material based on the covalent organic framework energy absorption in this embodiment is 4.9MJ / m 2 The flexural strength is 11.8MPa, the compressive strength is 54MPa, the bonding strength is 2.2MPa, the fluidity is 42s, and the setting time is 24min.

[0173] Example 5 (the content of covalent organic framework single crystal is 4 parts of the lower limit of this application, and the rest is the same as Example 1)

[0174] This embodiment is basically the same as Embodiment 1, except that:

[0175] Grouting materials based on covalent organic framework energy absorption:

[0176] The grouting material based on covalent organic framework energy absorption is composed of the following components in parts by mass: 4 parts of covalent organic framework single crystals, 1 part of early strength agent, 0.5 parts of accelerator, 0.5 parts of toughening agent, 0.3 parts of water retaining agent, 1 part of reinforcing agent, and 100 parts of ferroaluminate clinker.

[0177] In the preparation method of the grouting material based on the covalent organic framework energy absorption:

[0178] In step S103, the amount of the covalent organic framework single crystal used is 4 parts by mass.

[0179] Weigh 2 kg of the grouting material prepared in this embodiment, mix it evenly with deionized water in a mass ratio of 1:1, and test the bonding strength of the slurry with reference to the national standard GB / T29756-2013; prepare the slurry into a test block of 40 mm × 40 mm × 160 mm, and test the bonding strength of the slurry with reference to the national standard GB / T 17671-2021 to characterize the compressive strength of the material.

[0180] After testing, the impact resistance of the grouting material based on the covalent organic framework energy absorption in this embodiment is 4.5MJ / m 2 The flexural strength is 11.5MPa, the compressive strength is 47MPa, the bonding strength is 2.1MPa, the fluidity is 44s, and the setting time is 23min.

[0181] Example 6 (the content of covalent organic framework single crystal is 6 parts of the upper limit of this application, and the rest is the same as Example 1)

[0182] This embodiment is basically the same as Embodiment 1, except that:

[0183] Grouting materials based on covalent organic framework energy absorption:

[0184] The grouting material based on covalent organic framework energy absorption is composed of the following components in parts by mass: 6 parts of covalent organic framework single crystals, 1 part of early strength agent, 0.5 parts of accelerator, 0.5 parts of toughening agent, 0.3 parts of water retaining agent, 1 part of reinforcing agent, and 100 parts of ferroaluminate clinker.

[0185] In the preparation method of the grouting material based on the covalent organic framework energy absorption:

[0186] In step S103, the amount of the covalent organic framework single crystal used is 6 parts by mass.

[0187] Weigh 2 kg of the grouting material prepared in this embodiment, mix it evenly with deionized water in a mass ratio of 1:1, and test the bonding strength of the slurry with reference to the national standard GB / T29756-2013; prepare the slurry into a test block of 40 mm × 40 mm × 160 mm, and test the bonding strength of the slurry with reference to the national standard GB / T 17671-2021 to characterize the compressive strength of the material.

[0188] After testing, the impact resistance of the grouting material based on the covalent organic framework energy absorption in this embodiment is 7.0MJ / m 2 , flexural strength is 13.8MPa, compressive strength is 70MPa, bonding strength is 2.5, fluidity is 38s, and setting time is 22min.

[0189] Example 7 (the content of aluminoferrate clinker is 80 parts of the lower limit of this application, and the rest is the same as Example 1)

[0190] This embodiment is basically the same as Embodiment 1, except that:

[0191] Grouting materials based on covalent organic framework energy absorption:

[0192] The grouting material based on covalent organic framework energy absorption is composed of the following components in parts by weight: 5 parts of covalent organic framework single crystals, 1 part of early strength agent, 0.5 parts of accelerator, 0.5 parts of toughening agent, 0.3 parts of water retaining agent, 1 part of reinforcing agent, and 80 parts of ferroaluminate clinker.

[0193] In the preparation method of the grouting material based on the covalent organic framework energy absorption:

[0194] In step S103, the amount of aluminoferrite clinker used is 80 parts by mass.

[0195] Weigh 2 kg of the grouting material prepared in this embodiment, mix it evenly with deionized water in a mass ratio of 1:1, and test the bonding strength of the slurry with reference to the national standard GB / T29756-2013; prepare the slurry into a test block of 40 mm × 40 mm × 160 mm, and test the bonding strength of the slurry with reference to the national standard GB / T 17671-2021 to characterize the compressive strength of the material.

[0196] After testing, the impact resistance of the grouting material based on the covalent organic framework energy absorption in this embodiment is 4.7MJ / m 2 The flexural strength is 11.9MPa, the compressive strength is 53MPa, the bonding strength is 2.1MPa, the fluidity is 44s, and the setting time is 29min.

[0197] Example 8 (the content of aluminoferrite clinker is 120 parts of the upper limit of this application, and the rest is the same as Example 1)

[0198] This embodiment is basically the same as Embodiment 1, except that:

[0199] Grouting materials based on covalent organic framework energy absorption:

[0200] The grouting material based on covalent organic framework energy absorption is composed of the following components in parts by mass: 5 parts of covalent organic framework single crystals, 1 part of early strength agent, 0.5 parts of accelerator, 0.5 parts of toughening agent, 0.3 parts of water retaining agent, 1 part of reinforcing agent, and 120 parts of ferroaluminate clinker.

[0201] In the preparation method of the grouting material based on the covalent organic framework energy absorption:

[0202] In step S103, the amount of aluminoferrite clinker used is 120 parts by mass.

[0203] Weigh 2 kg of the grouting material prepared in this embodiment, mix it evenly with deionized water in a mass ratio of 1:1, and test the bonding strength of the slurry with reference to the national standard GB / T29756-2013; prepare the slurry into a test block of 40 mm × 40 mm × 160 mm, and test the bonding strength of the slurry with reference to the national standard GB / T 17671-2021 to characterize the compressive strength of the material.

[0204] After testing, the impact resistance of the grouting material based on the covalent organic framework energy absorption in this embodiment is 4.8MJ / m 2 The flexural strength is 12.1MPa, the compressive strength is 55MPa, the bonding strength is 2.2MPa, the fluidity is 42s, and the setting time is 19min.

[0205] Example 9 (the content of the covalent organic framework single crystal is the same as that of Example 1, and the contents of other components are all lower limits)

[0206] This embodiment is basically the same as Embodiment 1, except that:

[0207] Grouting materials based on covalent organic framework energy absorption:

[0208] The grouting material based on covalent organic framework energy absorption is composed of the following components in parts by mass: 5 parts of covalent organic framework single crystal, 0.8 parts of early strength agent, 0.4 parts of accelerator, 0.4 parts of toughening agent, 0.24 parts of water retaining agent, 0.8 parts of reinforcing agent and 80 parts of ferroaluminate clinker.

[0209] In the preparation method of the grouting material based on the covalent organic framework energy absorption:

[0210] In step S103, 5 parts of the covalent organic framework single crystal obtained in step S102, 0.8 parts of an early strength agent, 0.4 parts of a coagulant, 0.4 parts of a toughening agent, 0.24 parts of a water retaining agent, and 0.8 parts of a reinforcing agent are weighed by mass and added to 80 parts of alumina-ferroferrocement cementitious material.

[0211] Weigh 2 kg of the grouting material prepared in this embodiment, mix it evenly with deionized water in a mass ratio of 1:1, and test the bonding strength of the slurry with reference to the national standard GB / T29756-2013; prepare the slurry into a test block of 40 mm × 40 mm × 160 mm, and test the bonding strength of the slurry with reference to the national standard GB / T 17671-2021 to characterize the compressive strength of the material.

[0212] After testing, the impact resistance of the grouting material based on the covalent organic framework energy absorption in this embodiment is 4.4MJ / m 2 The flexural strength is 10.8MPa, the compressive strength is 47MPa, the bonding strength is 2.0MPa, the fluidity is 45s, and the setting time is 27min.

[0213] Example 10 (the content of the covalent organic framework single crystal is the same as that of Example 1, and the contents of other components are all upper limits)

[0214] This embodiment is basically the same as Embodiment 1, except that:

[0215] Grouting materials based on covalent organic framework energy absorption:

[0216] The grouting material based on covalent organic framework energy absorption is composed of the following components in parts by weight: 5 parts of covalent organic framework single crystal, 1.2 parts of early strength agent, 0.6 parts of accelerator, 0.6 parts of toughening agent, 0.36 parts of water retaining agent, 1.2 parts of reinforcing agent and 120 parts of ferroaluminate clinker.

[0217] In the preparation method of the grouting material based on the covalent organic framework energy absorption:

[0218] In step S103, 5 parts of the covalent organic framework single crystal obtained in step S102, 1.2 parts of an early strength agent, 0.6 parts of a coagulant, 0.6 parts of a toughening agent, 0.36 parts of a water retaining agent, and 1.2 parts of a reinforcing agent are weighed by mass and added to 120 parts of alumina-ferrocement clinker cementitious material.

[0219] Weigh 2 kg of the grouting material prepared in this embodiment, mix it evenly with deionized water in a mass ratio of 1:1, and test the bonding strength of the slurry with reference to the national standard GB / T29756-2013; prepare the slurry into a test block of 40 mm × 40 mm × 160 mm, and test the bonding strength of the slurry with reference to the national standard GB / T 17671-2021 to characterize the compressive strength of the material.

[0220] After testing, the impact resistance of the grouting material based on the covalent organic framework energy absorption in this embodiment is 5.9MJ / m 2 The flexural strength is 12.8MPa, the compressive strength is 60MPa, the bonding strength is 2.4MPa, the fluidity is 43s, and the setting time is 22min.

[0221] Example 11 (the covalent organic framework single crystal is a commercially available product, and the rest is the same as Example 1)

[0222] This embodiment is basically the same as Embodiment 1, except that:

[0223] In the grouting material based on covalent organic framework energy absorption, the covalent organic framework single crystal is a covalent organic framework single crystal of model COF-22 produced by Beijing Beike New Materials Technology Co., Ltd.

[0224] The preparation method of the grouting material based on covalent organic framework energy absorption does not include step S101 and step S102, and the covalent organic framework single crystal in step S3 is the covalent organic framework single crystal in the grouting material based on covalent organic framework energy absorption of this embodiment.

[0225] Weigh 2 kg of the grouting material prepared in this embodiment, mix it evenly with deionized water in a mass ratio of 1:1, and test the bonding strength of the slurry with reference to the national standard GB / T29756-2013; prepare the slurry into a test block of 40 mm × 40 mm × 160 mm, and test the bonding strength of the slurry with reference to the national standard GB / T 17671-2021 to characterize the compressive strength of the material.

[0226] After testing, the impact resistance of the grouting material based on the covalent organic framework energy absorption in this embodiment is 3.9MJ / m 2 The flexural strength is 8.4MPa, the compressive strength is 35MPa, the bonding strength is 1.8MPa, the fluidity is 49s, and the setting time is 31min.

[0227] Example 12 (the catalyst is only zinc chloride, and the rest is the same as Example 1)

[0228] This embodiment is basically the same as Embodiment 1, except that:

[0229] Grouting materials based on covalent organic framework energy absorption:

[0230] The surface area of ​​the covalent organic framework single crystal is 210 m 2 / g; The covalent organic framework single crystal has micropores and mesopores, the average pore diameter of the micropores is 13nm, the average pore diameter of the mesopores is 66nm, and the porosity is 43%.

[0231] In the preparation method of the grouting material based on the covalent organic framework energy absorption:

[0232] In step S102, the catalyst is zinc chloride.

[0233] Weigh 2 kg of the grouting material prepared in this embodiment, mix it evenly with deionized water in a mass ratio of 1:1, and test the bonding strength of the slurry with reference to the national standard GB / T29756-2013; prepare the slurry into a test block of 40 mm × 40 mm × 160 mm, and test the bonding strength of the slurry with reference to the national standard GB / T 17671-2021 to characterize the compressive strength of the material.

[0234] After testing, the impact resistance of the grouting material based on the covalent organic framework energy absorption in this embodiment is 3.8MJ / m 2 The flexural strength is 9.4MPa, the compressive strength is 37MPa, the bonding strength is 1.7MPa, the fluidity is 45s, and the setting time is 29min.

[0235] Example 13 (the catalyst is only stannous octoate, and the rest is the same as Example 1)

[0236] This embodiment is basically the same as Embodiment 1, except that:

[0237] Grouting materials based on covalent organic framework energy absorption:

[0238] The specific surface area of ​​the covalent organic framework single crystal is 226m 2 / g; the covalent organic framework single crystal has micropores and mesopores, the average pore diameter of the micropores is 10nm, the average pore diameter of the mesopores is 58nm, and the porosity is 57%.

[0239] In the preparation method of the grouting material based on the covalent organic framework energy absorption:

[0240] In step S102, the catalyst is stannous octoate.

[0241] Weigh 2 kg of the grouting material prepared in this embodiment, mix it evenly with deionized water in a mass ratio of 1:1, and test the bonding strength of the slurry with reference to the national standard GB / T29756-2013; prepare the slurry into a test block of 40 mm × 40 mm × 160 mm, and test the bonding strength of the slurry with reference to the national standard GB / T 17671-2021 to characterize the compressive strength of the material.

[0242] After testing, the impact resistance of the grouting material based on the covalent organic framework energy absorption in this embodiment is 3.7MJ / m 2 The flexural strength is 8.3MPa, the compressive strength is 39MPa, the bonding strength is 1.9MPa, the fluidity is 46s, and the setting time is 30min.

[0243] Comparative Example 1 (excluding covalent organic framework single crystal, the rest is the same as Example 1)

[0244] This comparative example is basically the same as Example 1, except that:

[0245] The grouting material based on covalent organic framework energy absorption does not contain covalent organic framework single crystals.

[0246] The method for preparing a grouting material based on covalent organic framework energy absorption does not include step S101 and step S102, and step S3 does not include a covalent organic framework single crystal.

[0247] Weigh 2 kg of the grouting material prepared in this embodiment, mix it evenly with deionized water in a mass ratio of 1:1, and test the bonding strength of the slurry with reference to the national standard GB / T29756-2013; prepare the slurry into a test block of 40 mm × 40 mm × 160 mm, and test the bonding strength of the slurry with reference to the national standard GB / T 17671-2021 to characterize the compressive strength of the material.

[0248] After testing, the impact resistance of the grouting material based on the covalent organic framework energy absorption in this embodiment is 2.6MJ / m 2 The flexural strength is 6.7MPa, the compressive strength is 32MPa, the bonding strength is 1.7MPa, the fluidity is 48s, and the setting time is 33min.

[0249] Comparative Example 2 (the content of covalent organic framework single crystal is lower than the lower limit of this application, and the rest is the same as Example 1)

[0250] This comparative example is basically the same as Example 1, except that:

[0251] Grouting materials based on covalent organic framework energy absorption:

[0252] The grouting material based on covalent organic framework energy absorption is composed of the following components in parts by weight: 3 parts of covalent organic framework single crystals, 1 part of early strength agent, 0.5 parts of accelerator, 0.5 parts of toughening agent, 0.3 parts of water retaining agent, 1 part of reinforcing agent, and 100 parts of ferroaluminate clinker.

[0253] In the preparation method of the grouting material based on the covalent organic framework energy absorption:

[0254] In step S103, the amount of the covalent organic framework single crystal used is 3 parts by mass.

[0255] Weigh 2 kg of the grouting material prepared in this embodiment, mix it evenly with deionized water in a mass ratio of 1:1, and test the bonding strength of the slurry with reference to the national standard GB / T29756-2013; prepare the slurry into a test block of 40 mm × 40 mm × 160 mm, and test the bonding strength of the slurry with reference to the national standard GB / T 17671-2021 to characterize the compressive strength of the material.

[0256] After testing, the impact resistance of the grouting material based on the covalent organic framework energy absorption in this embodiment is 3.2MJ / m 2 The flexural strength is 9.4MPa, the compressive strength is 35MPa, the bonding strength is 1.9MPa, the fluidity is 47s, and the setting time is 30min.

[0257] Comparative Example 3 (the content of covalent organic framework single crystal is higher than the upper limit of this application, and the rest is the same as Example 1)

[0258] This comparative example is basically the same as Example 1, except that:

[0259] Grouting materials based on covalent organic framework energy absorption:

[0260] The grouting material based on covalent organic framework energy absorption is composed of the following components in parts by weight: 7 parts of covalent organic framework single crystal, 1 part of early strength agent, 0.5 parts of accelerator, 0.5 parts of toughening agent, 0.3 parts of water retaining agent, 1 part of reinforcing agent, and 100 parts of ferroaluminate clinker.

[0261] In the preparation method of the grouting material based on the covalent organic framework energy absorption:

[0262] In step S103, the amount of the covalent organic framework single crystal used is 7 parts by mass.

[0263] Weigh 2 kg of the grouting material prepared in this embodiment, mix it evenly with deionized water in a mass ratio of 1:1, and test the bonding strength of the slurry with reference to the national standard GB / T29756-2013; prepare the slurry into a test block of 40 mm × 40 mm × 160 mm, and test the bonding strength of the slurry with reference to the national standard GB / T 17671-2021 to characterize the compressive strength of the material.

[0264] After testing, the impact resistance of the grouting material based on the covalent organic framework energy absorption in this embodiment is 4.0MJ / m 2 The flexural strength is 9.9MPa, the compressive strength is 38MPa, the bonding strength is 1.9MPa, the fluidity is 49s, and the setting time is 30min.

[0265] Comparative Example 4 (the preparation method does not contain a catalyst, and the rest is the same as Example 1)

[0266] This comparative example is basically the same as Example 1, except that:

[0267] The preparation method of the grouting material based on the covalent organic framework energy absorption does not contain a catalyst.

[0268] Weigh 2 kg of the grouting material prepared in this embodiment, mix it evenly with deionized water in a mass ratio of 1:1, and test the bonding strength of the slurry with reference to the national standard GB / T29756-2013; prepare the slurry into a test block of 40 mm × 40 mm × 160 mm, and test the bonding strength of the slurry with reference to the national standard GB / T 17671-2021 to characterize the compressive strength of the material.

[0269] After testing, the impact resistance of the grouting material based on the covalent organic framework energy absorption in this embodiment is 3.1MJ / m 2 The flexural strength is 7.6MPa, the compressive strength is 34MPa, the bonding strength is 1.8MPa, the fluidity is 47s, and the setting time is 31min.

[0270] Comparative Example 5 (the preparation method and catalyst are existing catalysts, and the rest are the same as Example 1)

[0271] This comparative example is basically the same as Example 1, except that:

[0272] In the preparation method of the grouting material based on the covalent organic framework energy absorption, the catalyst is benzoic anhydride.

[0273] Weigh 2 kg of the grouting material prepared in this embodiment, mix it evenly with deionized water in a mass ratio of 1:1, and test the bonding strength of the slurry with reference to the national standard GB / T29756-2013; prepare the slurry into a test block of 40 mm × 40 mm × 160 mm, and test the bonding strength of the slurry with reference to the national standard GB / T 17671-2021 to characterize the compressive strength of the material.

[0274] After testing, the impact resistance of the grouting material based on the covalent organic framework energy absorption in this comparative example is 3.7MJ / m 2 The flexural strength is 9.1MPa, the compressive strength is 41MPa, the bonding strength is 1.8MPa, the fluidity is 49s, and the setting time is 34min.

[0275] In the present application, the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. mean that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the described specific features, structures, materials or characteristics may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0276] Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations on the present application. Ordinary technicians in this field can change, modify, replace and modify the above embodiments within the scope of the present application.

Claims

1. A grouting material based on covalent organic framework energy absorption, characterized in that: The invention comprises the following components in parts by weight: 4-6 parts of covalent organic framework single crystal, 0.8-1.2 parts of early strength agent, 0.4-0.6 parts of coagulant, 0.4-0.6 parts of toughening agent, 0.24-0.36 parts of water retaining agent, 0.8-1.2 parts of reinforcing agent, and 80-120 parts of ferroaluminate clinker cementitious material; The covalent organic framework single crystal has micropores and / or mesopores, and the covalent organic framework single crystal has at least one of the following characteristics: (1) Specific surface area is 100-1500m 2 / g; (2) The average pore size of the micropores is 1-2 nm; (3) The average pore size of the mesopores is 2-50 nm; (4) Porosity is 70-90%; The method for preparing the covalent organic framework single crystal comprises: dissolving the carbon source in a solvent to obtain a uniform solution; subjecting at least a portion of the uniform solution to an organic covalent reaction under the action of a catalyst, followed by filtering and drying to obtain the covalent organic framework single crystal; The carbon source includes at least one of 4,4′-(1,10-phenanthroline-2,9-diyl)diphenylamine, tetrakis(4-formylphenyl)ethylene, and tetrakis(4-borylphenyl)ethylene; The catalyst includes at least one of zinc chloride and stannous octoate.

2. The grouting material based on covalent organic framework energy absorption according to claim 1, characterized in that: The invention comprises the following components in parts by weight: 4.5-5.5 parts of covalent organic framework single crystal, 0.9-1.1 parts of early strength agent, 0.45-0.55 parts of coagulant, 0.45-0.55 parts of toughening agent, 0.27-0.33 parts of water retaining agent, 0.9-1.1 parts of reinforcing agent and 90-110 parts of ferroaluminate clinker cementitious material.

3. The grouting material based on covalent organic framework energy absorption according to claim 2, characterized in that: The invention comprises the following components in parts by weight: 5 parts of covalent organic framework single crystal, 1 part of early strength agent, 0.5 part of accelerator, 0.5 part of toughening agent, 0.3 part of water retaining agent, 1 part of reinforcing agent and 100 parts of ferroaluminate clinker cementitious material.

4. The grouting material based on covalent organic framework energy absorption according to any one of claims 1 to 3, characterized in that: The early strength agent includes at least one of cesium chloride, cesium sulfide and cesium nitrate; And / or, the coagulant includes at least one of sodium polyacrylate, polyethyleneimine, and sodium polyethylene sulfonate; And / or, the toughening agent includes at least one of polyvinyl chloride-butadiene block copolymer nanoparticles and polyethylene-propylene-isoprene block copolymer nanoparticles; And / or, the water retaining agent includes at least one of sodium 3-chloro-2-hydroxypropane sulfonate and sodium carboxymethyl starch; And / or, the reinforcing agent includes at least one of nano-silicon carbide particles, polydopamine nano-particles, and nano-cobalt oxide particles.

5. The grouting material based on covalent organic framework energy absorption according to claim 4, characterized in that: The early strength agent is composed of cesium chloride, cesium sulfide and cesium nitrate, and the mass ratio of cesium chloride, cesium sulfide and cesium nitrate is 1: (1.6-2.4): 1; And / or, the coagulant is composed of sodium polyacrylate, polyethyleneimine, and sodium polyethylene sulfonate, and the mass ratio of sodium polyacrylate, polyethyleneimine, and sodium polyethylene sulfonate is 1:(2.4-3.6):1; And / or, the toughening agent is composed of polyvinyl chloride-butadiene block copolymer nanoparticles and polyethylene-propylene-isoprene block copolymer nanoparticles, and the mass ratio of the polyvinyl chloride-butadiene block copolymer nanoparticles to the polyethylene-propylene-isoprene block copolymer nanoparticles is 1:(1.6-2.4); And / or, the water retaining agent is composed of sodium 3-chloro-2-hydroxypropane sulfonate and sodium carboxymethyl starch, and the mass ratio of sodium 3-chloro-2-hydroxypropane sulfonate to sodium carboxymethyl starch is (2.4-3.6): 1; And / or, the reinforcing agent is composed of nano-silicon carbide particles, polydopamine nano-particles and nano-cobalt oxide particles, and the mass ratio of the nano-silicon carbide particles, the polydopamine nano-particles and the nano-cobalt oxide particles is 1:1:(4-6).

6. A method for preparing a grouting material based on covalent organic framework energy absorption according to any one of claims 1 to 5, characterized in that: include: The covalent organic framework single crystal, early strength agent, accelerator, toughening agent, water retaining agent, reinforcing agent and aluminoferrite clinker gelling material are mixed in a formula amount to obtain the grouting material based on covalent organic framework energy absorption.

7. The preparation method according to claim 6, characterized in that: The method for preparing the grouting material based on the covalent organic framework energy absorption also includes the step of preparing the covalent organic framework single crystal; the method for preparing the covalent organic framework single crystal includes: dissolving the carbon source in a solvent to obtain a uniform solution; At least a portion of the uniform solution is subjected to an organic covalent reaction under the action of a catalyst, and then filtered and dried to obtain the covalent organic framework single crystal.

8. The preparation method according to claim 7, characterized in that: The carbon source includes at least one of 4,4′-(1,10-phenanthroline-2,9-diyl)diphenylamine, tetrakis(4-formylphenyl)ethylene, and tetrakis(4-borylphenyl)ethylene; and / or, the solvent is a non-polar solvent; And / or, the method of dissolving the carbon source in the solvent includes at least one of heating, stirring, ultrasonic dispersion, and ball milling; And / or, the catalyst comprises at least one of zinc chloride and stannous octoate; And / or, the amount of the catalyst is 1-5wt% of the amount of the carbon source; And / or, the organic covalent reaction is carried out in a microwave reaction tube; And / or, the temperature of the organic covalent reaction is 100-120° C., and the time of the organic covalent reaction is 1.5-3 h.

9. Application of the grouting material based on covalent organic framework energy absorption as described in any one of claims 1 to 5 or the grouting material based on covalent organic framework energy absorption prepared by the preparation method of the grouting material based on covalent organic framework energy absorption as described in any one of claims 6 to 8 in the field of surrounding rock control of coal mine tunnels with rock burst.

Citation Information

Patent Citations

  • Double-doped grouting material for repairing pavement and preparation method of double-doped grouting material

    CN107840626A

  • Flexible reinforced grouting material and preparation method thereof

    CN117024086A

  • Preparation method of self-repairing material based on reinforced and toughened covalent organic framework filler

    CN118185046A